Baptist identity and mission in a rainbow nation: Distilling imperatives from mixed-methods research within the Baptist Union of Southern Africa (1994–2012) - Henry, Desmond (HTS teologiese studies, 2015)
The Baptist Union of Southern Africa’s (hereafter BUSA) future is conspicuous unless it understands the context within which it ministers in our ‘rainbow nation’. As a union of churches, BUSA faces significant challenges that have been highlighted through a mixed methods research approach. Through many months of data collection at the Baptist Union archives, an online survey and informal interviews spanning many parts of South Africa, the researcher practically demonstrates the importance of the cumulative results for the future of BUSA. This article highlights, in overview fashion, a few of the major challenges that need to be urgently addressed in the light of BUSA’s historic ecclesiological presuppositions that have their roots in the missional ministry of Hugo Gutshe who saw each of his Baptist congregants as missionary, and expanded the influence of BUSA in South Africa.